THE ECHO CHAMBER PHENOMENON IN DIGITAL PUBLIC SPACE: POLITICAL DISCOURSE AMONG GENERATION Z ON SOCIAL MEDIA (A COMPARATIVE STUDY OF INDONESIA-THAILAND) - Dewi Ariyanti Soffi; Widowati Widowati; Mas Adam Lukman Chaubah (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study examines the phenomenon of echo chambers in the digital public sphere and its implications for the formation of political opinions among Generation Z on social media, through a comparative analysis of Indonesia and Thailand. The rapid development of information technology has positioned social media as a primary arena for participatory public discourse, while simultaneously fostering information fragmentation driven by algorithmic personalization. This research aims to analyze the formation of echo chambers and their impact on the quality of political discourse by employing the theoretical frameworks of Jürgen Habermas’s public sphere, network society, and filter bubble. A qualitative approach with a netnographic method was applied, focusing on observations of TikTok, Instagram, and X. The data, consisting of digital interactions such as posts, comments, and political narratives, were analyzed using Critical Discourse Analysis (CDA). The findings reveal that echo chambers emerge from the interaction between individual cognitive biases, homogeneous social networks, and platform algorithms that reinforce content personalization. This condition contributes to political polarization, limits the diversity of perspectives, and constrains the development of an inclusive and deliberative public sphere. Comparatively, in Indonesia, echo chambers are largely shaped by electoral competition and popular digital culture, whereas in Thailand they are more closely linked to power relations and state control over digital spaces. These findings indicate a transformation and degradation of the digital public sphere, where opinion formation is increasingly dominated by the reproduction of homogeneous narratives rather than rational-critical debate. Therefore, strengthening digital literacy and critical awareness is essential to sustain an open and democratic digital public sphere.